Application Of The User Experience Lifecycle Method On Thesis Data Processing Information System And Stmik Field Work Practice Report YMI Tegal - Arif, Zaenul (Journal of World Science, 2022)
Educational institutions really need a data processing information system in carrying out their work activities because they are seen to be more organized and directed with the support of adequate computer equipment. STMIK YMI Tegal is a computer-based high school, but at the UPT bureau of the library as the inventory and management of PKL and Thesis reports, there is no information system facility for processing data on PKL and Thesis report titles. In its management, it still uses the manual method, which is recorded in a ledger, so it feels slow and not well organized. So in this study, the author tries to create a Data Processing Information System for PKL Reports and Thesis, which is specifically to provide information on title data for PKL reports and Thesis to the academic community of STMIK YMI Tegal. The method used in this study is the User Experience Lifecycle method, which is the method proposed by Hartson and Pyla to develop user experience by focusing on usability and user experience aspects. This method is divided into four stages, namely analysis, design, prototype, and evaluation. With this PKL and Thesis Report Data Processing Information System, it is expected to be able to help the UPT Library bureau in processing PKL and Thesis report title data and make it easier for students to search for PKL or Thesis report titles online